Narasi Kearifan Lokal Gerabah Pademawu sebagai Bahan Ajar Bahasa Indonesia Bermuatan Seni Madura (Narrative of Local Wisdom of Pademawu Pottery as Teaching Material Indonesian Containing Madurese Art) - Mohammad Rifki; Ari Ambarwati (Jurusan Tadris Bahasa Indonesia, 2023)
This study focuses on describing Pademawu pottery which is used as teaching materials for Indonesian Madurean art. The Pademawu community is one of the producers of pottery with the best quality, pottery products have been widely exported abroad. Pademawu pottery contains the values of local wisdom at every stage of its manufacture so that it is strategically arranged as teaching materials for Indonesians. The research method is qualitative descriptive with an ethnographic approach to obtain an overview of the content of virtue and wisdom in Pademawu pottery that can be implemented in Indonesian subjects. The novelty of this research is the study of the narrative of Madurese wisdom on Pademawu pottery as teaching material for Indonesians, especially in affective and psychomotor aspects. The results showed that there is material content in pottery related to the basic competencies of the 2013 Curriculum so it has the potential to be used as teaching materials for Indonesian adaptive Madurese local wisdom.Penelitian ini berfokus mendeskripsikan gerabah Pademawu yang digunakan sebagai bahan ajar Bahasa Indonesia bermuatan seni Madura. Masyarakat Pademawu merupakan salah satu produsen gerabah dengan kualitas terbaik, hasil gerabah sudah banyak diekspor ke luar negeri. Gerabah Pademawu mengandung nilai-nilai kearifan lokal pada setiap tahap pembuatannya sehingga strategis disusun sebagai bahan ajar Bahasa Indonesia. Metode penelitian ialah deskriptif kualitatif dengan pendekatan etnografi untuk memperoleh gambaran muatan kebajikan dan kebijaksanaan pada gerabah Pademawu yang dapat diimplementasikan dalam mata pelajaran Bahasa Indonesia. Kebaruan penelitian ini adalah kajian narasi kearifan Madura pada gerabah Pademawu sebagai bahan ajar Bahasa Indonesia, khususnya dalam aspek afektif dan psikomotorik. Hasil penelitian menunjukkan bahwa terdapat muatan materi yang ada pada gerabah yang berkaitan dengan kompetensi dasar Kurikulum 2013 sehingga berpotensi dijadikan bahan ajar Bahasa Indonesia adaptif kearifan lokal Madura.